Implementasi Upaya Restorative Justice terhadap Tindak Pidana Pelecehan Seksual Berdasarkan Perpol Nomor 8 Tahun 2021: Studi Kasus Polres Sleman - Maliki Sirojudin Agani; Mo’amer Kohsad; Bonifasius Deanka Pramoedya Ekarossa; Irfa’i Fadlullah (Pusat Riset dan Inovasi Nasional, 2026)
This article examines the handling of sexual harassment offenses within Indonesia’s criminal justice system, which faces complex challenges, particularly when restorative justice (RJ) is used as an alternative mechanism for case resolution. This study analyzes the implementation of RJ in sexual harassment cases at the Sleman Resort Police (Polres Sleman), referring to the Indonesian National Police Regulation No. 8 of 2021 on the Handling of Criminal Acts Based on Restorative Justice. The analysis focuses on how this policy is applied at the operational level and how its practice interacts with the normative provisions set forth in Law No. 12 of 2022 on Sexual Violence Crimes (UU TPKS), which explicitly prohibits non-judicial settlement for several categories of sexual violence. Using a qualitative approach through interviews, observations, and document analysis, the study finds that RJ continues to be applied at Polres Sleman despite its potential conflict with the prohibitions stipulated in the UU TPKS. At the operational level, the legal culture of police officers plays a significant role in encouraging the use of RJ, driven by pragmatic considerations such as efficiency in case resolution, social pressure from the community, and officers’ perceptions of the seriousness of sexual harassment cases. As a result, victims’ rights often fail to become the central focus, even though victimology emphasizes the importance of victim recovery and protection. The study concludes that regulatory harmonization, increased sensitivity of law enforcement officers toward sexual violence issues, and strengthened victim protection mechanisms are essential to ensure that the application of RJ does not undermine substantive justice.